Understanding the epistemological development of substance abusing college students: a construct exploration study - Miller, Lisa A., author; Kuk, Linda, advisor; Banning, James, advisor (Colorado State University. Libraries, 2009)
The purpose of this study was to delve into the epistemological constructs of substance abusing college students and explore whether consistencies with Baxter Magolda's (1992) epistemic constructs were indicated The study utilized a qualitative, narrative inquiry research design framed by Baxter Magolda's interview outline. Interviews were conducted with five, college, males each of who were in a leveraged, substance abuse, campus treatment model. All five men had experienced significant consequences related to substance abuse and had been assessed by substance abuse professionals. The same questions regarding the role of the learner, the role of the instructor, the role of peers, the role of evaluation, and the nature of knowledge were employed with each participant. The method of template analysis was utilized to examine and understand the rich narratives of participants by deductively searching for categories outlined by the theoretical underpinnings of cognitive theorists and inductively exploring emerging themes. The findings of the study revealed a consistency between the epistemic constructs of the participants and Baxter Magolda's (1992) epistemic constructs of absolute and transitional knowing The findings tentatively suggested that an epistemological delay was present among some participants. The emergence of voice and a utilitarian value of learning emerged as relevant themes regardless of the participant's epistemic construct. This study provides a foundation in understanding the significance of the epistemological development of substance abusing college students. The findings suggest that the epistemological development of college students may be an important consideration in designing and implementing substance abuse intervention strategies.
Keywords: college students; epistemological development; Magolda, Baxter; substance abuse; educational psychology; clinical psychology; higher education; epistemology; drug abuse; college students; constructivism